Effect of Papaya Seeds (Carica papaya) and Gandarusa Leaves (Justicia gendarussa) on the Spermatozoa Quality of Male Mice - Jangga Jangga; Abdul Wahid Suleman; Saparuddin Latu; Sri Wulan Rini (Universitas Sebelas Maret, 2024)
Papaya seeds (Carica papaya L.) and gandarusa leaves (Justicia gendarussa Burm.f.) are considered medicinal plants that can be used as natural male contraceptives. Papaya seeds contain alkaloids, triterpenoids, saponins, and papain. Meanwhile, the gandarusa leaves contain flavonoids. These compounds have the function of antifertility for men. The purpose of this study was to determine the effect of papaya seeds (Carica papaya L.) ethanol extracts, gandarusa leaves (Justicia gendarussa Burm.f.), and its combination on motility, viability, and morphology of male mice spermatozoa (Mus musculus) most effective decrease concentration on motility, viability, and morphology of male mice spermatozoa (Mus musculus). This research was an experimental study. The samples of this study were 18 male mice with a body weight of 20-30 grams, aged 3-5 months, and were divided into six groups. The treatments given were control, papaya seed ethanol extract, gandarusa leaves ethanol extract, and its combinations to concentrations of P1 Na CMC1%, P2 (papaya seed 100mg/kgW), P3 (gandarusa leaf 50mg/kgW), P4 (papaya seed : gandarusa leaf 50:50 mg/kgW), P5 (papaya seed : gandarusa leaf 50:100 mg/ kgW), P6 (papaya seed : gandarusa leaf 100:50 mg/kgW). The extract was given for 35 days. On the 36th day, the mice were dissected to take their epididymis to observe the spermatozoa's quality (motility, viability, morphology). Those observations used a light microscope. Data were analyzed using one-way ANOVA and LSD post hoc tests. This study resulted differences in P1, P2, P3, P4, P5, and P6 towards motility, viability, and morphology of spermatozoa (p< 0.05). The conclusion of this study showed that both single and combination ethanol extracts of papaya seeds and gandarusa leaves could reduce the motility, viability, and morphology of spermatozoa of male mice, and the effective dosage in reducing motility, viability, and morphology of spermatozoa is P3 gandarusa leaves 50mg/kgW.